Answer:
x = -1
Explanation:
We have given a quadratic equation.
x²+2x+1 = 0
We have to solve above equation by factoring.
Split the middle term of above equation so that the sum of two terms should be 2 and the product is 1, we have
x²+x+x+1 = 0
Making two groups and taking common, we have
x(x+1)+1(x+1) = 0
Taking (x+1) as common, we have
(x+1)(x+1) = 0
Applying Zero-Product Property to above equation, we have
x+1= 0 or x+1 = 0
x= -1 or x = -1
Both values are same.
Hence,
x = -1 is solution of given equation.